Labour Pain Intervention: A Bibliometrics Analysis - Nur Damayanti, Fitriani; Wiyanti, Zulvi; Pranata, Satria; Lutfitasari, Ariyani (Scripta Medica, 2024)
Pain and anxiety during childbirth are significant concerns during labour, especially in first-time mothers. This can increase labour time, increase stress hormones and affect the condition of the mother and newborn. This study aimed to determine trends in the number of publications on labour pain interventions, the number of citations and the direction of future research topics. The research method applied in this study was Preferred reporting items for systematic reviews and meta-analyses (PRISMA) which uses 158,201 scientific articles or proceedings sourced from the Dimensions database. Articles were reviewed by using the VOSviewer application. The results of the research revealed that the number of publications on the topic of labour pain intervention had an upward trend, the number of citations on the topic of labour pain intervention had increased. Network visualisation on the topic of labour pain intervention provided information to find newness on topics that were not yet connected, there were 4 clusters reviewing it from co-occurrence, overlay visualisation on the topic of labour pain intervention provided a trend towards future research topics, density visualisation on a topic that was still rare. The conclusion from the results of this research is that it contributes to the development of a research roadmap on labour pain interventions.